Does the Family Environment Matter? Examining Its Relationship with Elementary Students' Learning Motivation - Nur Annisa; Azizah Azizah; Nuraini Nuraini; Yusdin bin M Gagaramusu; Kasmawati Kasmawati (Journal of Innovation and Research in Primary Education, 2026)
The family environment is widely recognized as a foundational determinant of children's learning motivation; however, empirical evidence from urban-periphery communities in Indonesia—particularly those characterized by trade-based parental occupations—remains limited.  This quantitative correlational study involved all 23 fifth-grade students at SD Negeri 20 Palu, Central Sulawesi, recruited through total sampling. Data were collected using two validated Likert-scale questionnaires measuring family environment and learning motivation, supplemented by semi-structured interviews with teachers, the school principal, and selected parents. Data were analyzed using descriptive statistics, the Kolmogorov-Smirnov normality test, Pearson product-moment correlation, and coefficient of determination analysis with SPSS 25.  The family environment yielded a mean score of 77.03 (good category), while learning motivation yielded a mean of 84.59 (high category). Pearson correlation analysis revealed a significant moderate positive relationship between the two variables (r = 0.561, p = 0.004). The coefficient of determination indicated that the family environment accounted for 31.5% of the variance in learning motivation.  These findings align with Self-Determination Theory and the bioecological model, confirming that parental attention, emotional support, and a conducive home learning atmosphere are meaningful predictors of student motivation. The remaining 68.5% of unexplained variance underscores the complementary roles of school-based and individual-level factors.